EVALUATION OF ANTI-ANXIETY ACTIVITY OF ETHANOLIC EXTRACT OF RUBIA CORDIFOLIA (CAHIERS MAGELLANES-NS, 2024)
Anxiety is a prevalent neuropsychiatric disorder characterized by excessive worry, fear, and nervousness. The search for safer, natural alternatives to synthetic anxiolytics has led to the exploration of traditional medicinal plants. Rubia cordifolia, or Indian Madder, has been used in traditional medicine for various therapeutic purposes, but its anti-anxiety potential remains underexplored. This study aimed to evaluate the anxiolytic activity of the ethanolic extract of Rubia cordifolia and validate its traditional use. The extraction process yielded a 7.5% extract, with phytochemical analysis revealing the presence of key bioactive compounds including glycosides, flavonoids, phenolics, proteins, and diterpenes. Quantitative estimations showed a total phenol content (TPC) of 0.56 mg/100 mg and a total flavonoid content (TFC) of 0.72 mg/100 mg. Behavioral assays using the staircase and elevated plus-maze tests indicated that Rubia cordifolia extract significantly reduced exploratory behavior and increased time spent in open arms at a dose of 200 mg/kg, suggesting potential anxiolytic effects. In comparison, diazepam demonstrated stronger anxiolytic effects. These findings highlight Rubia cordifolia as a promising candidate for further research into natural anxiolytic agents, though its efficacy is currently less pronounced than that of diazepam.